A Philosophical Perspective of Pragmatism on the Intergenerational Reminiscence Model (IRM) on Health-Related Quality of Life among Older Adults - Sukardin Sukardin; Patcharee Komjakraphan; Ageng Abdi Putra (Caring: Indonesian Journal of Nursing Science, 2026)
The global increase in the older adult population necessitates the development of practical, evidence-based nursing interventions to address critical challenges to Health-Related Quality of Life (HRQoL), notably loneliness and a diminished sense of purpose. The Intergenerational Reminiscence Model (IRM), involving older adults sharing life experiences with younger generations, offers a highly promising psychosocial approach. This paper provides a conceptual analysis to philosophically ground the IRM within a pragmatist framework, arguing that this lens substantially enhances its theoretical rigor and effectively guides its future application in nursing science. Pragmatism is specifically chosen because its emphasis on action, experience, and practical consequences aligns perfectly with the IRM's primary objective of achieving measurable improvements in HRQoL. From an ontological perspective, pragmatism defines reality as dynamic, constructed actively through meaningful interactions older adults experience within their environments during intergenerational exchanges. Epistemologically, the core argument asserts that the true effectiveness of the IRM is strictly validated by its practical outcomes, specifically, its success in enhancing HRQoL. Axiologically, this framework prioritizes human flourishing, positioning observable improvements in HRQoL as the ultimate value claim. Methodologically, while this paper is philosophical, pragmatism provides robust theoretical justification for future empirical research utilizing mixed methods approaches. This is necessary to successfully capture quantitative results and the rich narratives of intergenerational experiences. Ultimately, pragmatism offers an ideal justification for a context-sensitive nursing intervention. Future research must utilize mixed methods to fully illustrate these benefits. In conclusion, pragmatism remains essential for advancing the IRM into a robust, evidence-based geriatric nursing model. Keyword: HRQoL, Intergenerational reminiscence model, Older adults, Pragmatism